Layanan Penguasaan Konten Dengan Teknik Sosial Modeling Untuk Mengurangi Perilaku Off Task Peserta Didik: Content Control Service With Social Techniques modeling To Reduce Behavior Off Task Of Students - Martina Rohama; Esty Aryani Safithry (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of this study was to determine the effectiveness of content mastery services with social modelling techniques to reduce off-task behaviour of Islamic students. The design of this study uses Single Subject Design (SSD) with multiple large cross variables. The subjects in this study were 5 class II MI HIdayatul students in the 2015/2016 academic year indicated as students who were off task behaving tending to be high and moderate, each of which was identified from the rubric of freedom of observation, intervention, and experimental control. Data analysis uses visual analysis by paying attention to changes in levels and trends.